Respuesta :
Answer:
a) The inverse is g(x) = (1/70)*x - 50/70
b) The slope intercept form is y = -6*x - 47
Step-by-step explanation:
a) When we have a function f(x), the inverse of this function (let's call it g(x)) is such that:
g(f(x)) = x
f(g(x)) = x
for every x.
In this case, we have:
f(x) = 70*x + 50
This is a linear function, and the inverse will be also a linear function.
Then the inverse will be something like:
g(x) = a*x + b
then:
g( f(x)) = x = a*( 70*x + 50) + b
then we can just solve the equation:
x = a*( 70*x + 50) + b
x = a*70*x + a*50 + b
If we separate terms by the powers of x in each side of the equation, we have:
1*x + 0*x^0 = (a*70)*x + (a*50 + b)*x^0
(where x^0 = 1)
then:
1 = (a*70)
a = 1/70
and:
0 = (a*50 + b)
0 = 50/70 + b
-50/70 = b
Then the inverse of f(x) is:
g(x) = (1/70)*x - 50/70.
b) The slop-intercept form of a linear equation is:
y = a*x + b
where a is the slope, and b is the y-intercept.
We want to write in this form the equation:
y + 5 = -6*(x + 7)
The first step is to isolate the "y" in one side of the equation:
y = -6*(x + 7) - 5
Now let's simplify the right side:
y = -6*x - 6*7 - 5
y = -6*x - 42 - 5
y = -6*x - 47
This is the slope-intercept form, where the slope is -6, and the y-intercept is -42.